Development of Accounting E-Module to Support the Scientific Approach of Students Grade X Vocational High School - Hamzah, Imron; Mentari, Sriyani (Journal of Accounting and Business Education, 2017)
Learning material development in form of electronic module with scientific is solution to optimize studentâs scientific thinking process in students. This electronic module development model uses ADDIE (Analysis, Design, Development and Implementation, Evaluation). Scientific approach to suports accounting e-module development is tested to students of grade X Accounting of SMK PGRI 2 Malang. Data type used is qualitative and quantitative. Test design used in scientific approach to suports e-module development is experimental. Data collection technique in this development uses polling. Research data analysis technique uses percentage descriptive technique, while qualitative data in form of critics and suggestion can directly make conclusion. Suports on scientific approach to suports accounting e-module development, from the result, it can be concluded that scientific approach to supports accounting e-module is appropriate and able to improve students learning motivation and result.Â Keywords: E-Module, Scientific Approach, Learning motivation, Learning result.